Landslide susceptibility mapping using logistic regression method and gis tool in Cameron Highlands - Yusrina, Mhamd Azizmy (2015)
This paper presents landslide susceptibility analysis around the Cameron Highlands area, Malaysia using a geographic information system (GIS) and remote sensing techniques. Topographical, geological data and satellite images were collected, processed, and constructed into a spatial database using GIS and image processing. Five landslide occurrence factors were selected as: topographic slope, topographic aspect, rainfall, geology map and land use from satellite images. Previous records of landslides in the study area were mapped based on inventory reports and satellite image processing. Landslide susceptibility map was then generated based on logistic regression equation in a raster GIS environment and classified in five susceptibility classes. The classes are divided into the study area has very low landslide susceptibility, low susceptibility, moderate susceptibility, high susceptibility and very high susceptibility. About 99.978% of the study area has very low landslide susceptibility, 0.003% has low susceptibility, 0.002% has moderate susceptibility, 0.001 % has high susceptibility and 0.015% has very high susceptibility